The Effect of Using Youtube in Teaching Vocabulary for First Year Students at SMA Negeri 1 Tanah Jawa - Dian Lasri Nababan; Yeni Lestari Simanjuntak (Indonesian Journal of Educational Science and Technology, 2023)
This research conducted at SMA Negeri 1 Tanah jawa which is located at Jalan. Balimbingan, Kec. Tanah Jawa, TanaH Jawa. The subjects of this study were students of class X 1 with a total of 11 students. The objectives of this study were  to find out whether there was a effectiveness of using offline YouTube video toward students’ vocabulary mastery 2) to improve the cognitive abilities of students on the vocabulary. The data collection techniques used are tests and observations. The researcher found that YouTube has many videos content which was useful for a students need, and is able to access everywhere. YouTube has become a new solution as a best media for learning and teaching. Data analysis revealed how YouTube tutorial videos could improve the students' speaking skill of the second-grade students of SMA Negeri 1 Tanah Jawa. This study used a quantitative approach and the experimental method with a quasi-experiment design of non-equivalent control group design. The research subjects were divided into two groups, namely the experimental group and the control group. The two groups were given pretest and posttest, then the results difference could later show whether the implementation of group exercises techniques was effective or not.